Inovasi Alat Penunjang Pembuatan Sediaan Histopatologi - Triwahyuni, Heni; Lasmijan, Lasmijan (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
The availability of supporting tools for histopathology slide preparation remains limited, characterized by high usage rates, inefficient material consumption, cleaning difficulties, frequent damage, high costs, small capacity, and low precision. This study aims to develop prototype innovations of supporting tools for histopathology preparation to address these issues. Three types of innovative tools were developed: a paraffin block mold, a slide rack for an automatic staining machine, and a slide box made of silicone-resin. The development process consisted of three main stages: the first mold creation (outer part), the second mold creation (inner part), and the casting of the innovative tools. The results demonstrate that the developed tools offer advantages in terms of effectiveness, efficiency, material savings, cost reduction, durability, and ease of production. Based on functionality testing, all tools were deemed feasible for use. This innovation is expected to serve as an alternative solution to the limited availability of supporting tools in the Anatomical Pathology Laboratory of the Faculty of Medicine, while also introducing a new approach through the use of different materials.